2018
DOI: 10.5812/jjm.58294
|View full text |Cite
|
Sign up to set email alerts
|

A Decline in Anti-Core+1 Antibody Titer Occurs in Successful Treatment of Patients Infected with Hepatitis C Virus

Abstract: Background: Hepatitis C virus (HCV) causes one of the major chronic liver diseases (CLD). HCV-core encoding sequence possesses an overlapping open reading frame (ORF) that expresses a protein called F or core+1. Objectives: The current study aimed at assessing the presence and titer of anti-core+1 antibody (Ab) in 70 Iranian patients infected with HCV-1a, responder and non-responder groups, under combination therapy with pegylated interferon-α (PegIFN-α) plus ribavirin (RBV) using an enzyme-linked immunosorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…HBV and HCV are associated with severe liver disease including chronic active hepatitis, cirrhosis, and hepatocellular carcinoma. [1][2][3][4] Evidence has shown that liver disease caused by hepatitis viruses can be more aggressive and severe in HIV carriers. 5 Globally, more than 71 million people globally have chronic hepatitis C infection, who are at a risk of developing liver cirrhosis and liver cancer, and causes 399,000 deaths every year.…”
Section: Introductionmentioning
confidence: 99%
“…HBV and HCV are associated with severe liver disease including chronic active hepatitis, cirrhosis, and hepatocellular carcinoma. [1][2][3][4] Evidence has shown that liver disease caused by hepatitis viruses can be more aggressive and severe in HIV carriers. 5 Globally, more than 71 million people globally have chronic hepatitis C infection, who are at a risk of developing liver cirrhosis and liver cancer, and causes 399,000 deaths every year.…”
Section: Introductionmentioning
confidence: 99%
“…29 Also, treatment with interferon may cause a decline in anti-F protein antibody in patients who responds to treatment. 30 Interestingly F protein antibody level is significantly higher in patients who do not respond to treatment. 30,31 These findings suggest a possible role in negative response to treatment.…”
Section: F Protein Propertiesmentioning
confidence: 98%
“…30 Interestingly F protein antibody level is significantly higher in patients who do not respond to treatment. 30,31 These findings suggest a possible role in negative response to treatment.…”
Section: F Protein Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…HCV infection is a serious global health problem and causes chronic hepatitis, liver cirrhosis, and HCC (Akuta et al 2007;Ajorloo et al 2015;Alborzi et al 2017Alborzi et al , 2015Moayedi et al 2018;Hashempoor et al 2018). It is estimated that 160 million people are infected worldwide (Lavanchy 2011).…”
Section: Introductionmentioning
confidence: 99%